Chromium toxicity induced oxidative damage in two rice cultivars and its mitigation through external supplementation of brassinosteroids and spermine. (September 2022) - Basit, Farwa; Bhat, Javaid Akhter; Dong, Zhang; Mou, Qingshan; Zhu, Xiaobo; Wang, Yang; Hu, Jin; Jan, Basit Latief; Shakoor, Awais; Guan, Yajing; Ahmad, Parvaiz
Abstract: The chromium (Cr) induced phytotoxicity avowed the scientific community to develop stress mitigation strategies to restrain the Cr accumulation inside the food chain. Whereas, brassinosteroids (BRs), and spermine (SPM) are well-known growth-promoting phytohormones, which enhance the plants health, and resilient the toxic effects under stress conditions. Until now, their interactive role against Cr-mitigation is poorly known. Hence, we conducted the hydroponic experiment to perceive the behavior of seed primed with BRs, or/and SPM treatment against Cr disclosure in two different rice cultivars (CY927; sensitive, YLY689; tolerant). Our findings delineated that BRs (0.01 μM), or/and SPM (0.01 mM) remarkably alleviated Cr-induced phytotoxicity by improving the seed germination ratio, chlorophyll pigments, PSII system, total soluble sugar, and minimizing the MDA contents level, ROS extra generation, and electrolyte leakage through restricting the Cr accretion in roots, and shoots of both rice cultivars under Cr stress. Additionally, the BRs, or/and SPM modulated the antioxidant enzyme, and non-enzyme activities to reduce the Cr-induced cellular oxidative damage as well as maintained the ionic hemostasis in both rice cultivars, especially in YLY689. Concisely, enhanced the plants biomass and growth. Overall, our outcomes revealed that BRs and SPM interact positively to alleviate the Cr-induced damages in rice seedlings on the above-mentioned indices, and combine treatment is much more efficient than solely. Moreover, the effect of BRs, or/and SPM was more obvious in YLY689 than CY927 to hamper the oxidative stress, and boost the antioxidant capacity. Graphical abstract: Image 1 Highlights: Chromium (Cr) toxicity affects growth and biochemical attributes in rice seedlings. The Cr also enhanced accumulation of Cr and disturbs the uptake of essential nutrients. Oxidative stress biomarkers and antioxidants enhanced under Cr toxicity. Brassinosteroids (BRs) and spermine (SPM) seed priming mitigates Cr toxicity through its restricted uptake. Primed seeds with BRs and SPM showed improvement in photosynthesis, and antioxidant activity under Cr stress.